2012
DOI: 10.1186/1471-2229-12-111
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a putative grapevine Zn transporter, VvZIP3, suggests its involvement in early reproductive development in Vitis vinifera L

Abstract: BackgroundZinc (Zn) deficiency is one of the most widespread mineral nutritional problems that affect normal development in plants. Because Zn cannot passively diffuse across cell membranes, it must be transported into intracellular compartments for all biological processes where Zn is required. Several members of the Zinc-regulated transporters, Iron-regulated transporter-like Protein (ZIP) gene family have been characterized in plants, and have shown to be involved in metal uptake and transport. This study d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 54 publications
2
43
1
Order By: Relevance
“…Interestingly, NsylIRT3 and NtomIRT3 transcripts are more abundant in flower tissues most likely for the redistribution of Zn and Fe. The function of Nicotiana IRT3 is possibly closer to the Zrt/IRT-like protein AtZIP4 , which is highly expressed in anther and pollen [61], where it is suspected to play a role in Zn redistribution in flowers ([62] and references therein). Thus, Zn and iron uptake is likely driven by AtIRT1 and AtIRT2 orthologous proteins in N. sylvestris , whereas another gene(s) is likely to perform this function in N. tomentosiformis .…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, NsylIRT3 and NtomIRT3 transcripts are more abundant in flower tissues most likely for the redistribution of Zn and Fe. The function of Nicotiana IRT3 is possibly closer to the Zrt/IRT-like protein AtZIP4 , which is highly expressed in anther and pollen [61], where it is suspected to play a role in Zn redistribution in flowers ([62] and references therein). Thus, Zn and iron uptake is likely driven by AtIRT1 and AtIRT2 orthologous proteins in N. sylvestris , whereas another gene(s) is likely to perform this function in N. tomentosiformis .…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that the ZmIRT1 , ZmZIP4 , ZmZIP5 and ZmZIP 6 contain cis -elements for seed expression (Additional file 7). Considering that there was some correlation between the VvZIP3 expression profile and the Zn accumulation pattern during the development of reproductive organs [42], we assumed that ZmIRT1 , ZmZIP4 , ZmZIP5 and ZmZIP6 may play various roles in both embryo and endosperm development.…”
Section: Discussionmentioning
confidence: 99%
“…The endogenous phytoene desaturase (PDS) gene and the magnesium chelatase subunit gene (Chl1) were both used as endogenous reporters to validate constructs inducing gene silencing in N. benthamania and tobacco plants (Golenberg et al, 2009;Ruiz et al, 1998). Inactivation of these genes results in loss of chlorophyll, leading to visible leaf bleaching.…”
Section: Endogenous Plant Genes As Silencing Reportersmentioning
confidence: 99%
“…Likewise, the ATP-binding cassette protein ABCC1 was localized to the tonoplast (Francisco et al, 2013). Particle bombardment of onion cells can also help investigate the localization of grapevine proteins, as shown for the zinc transporter ZIP3 in the plasma membrane (Gainza-Cort es et al, 2012). However, gene expression in heterologous systems may exhibit aberrant traits, presumably due to a foreign genetic background.…”
Section: Introductionmentioning
confidence: 99%